Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1039/d2tc05280f
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry breaking: an efficient structure design of nonfullerene acceptors to reduce the energy loss in organic solar cells

Abstract: In recent years, the innovative design of small-molecule non-fullerene acceptors (NFAs), in particular fused ring electron acceptors (FREAs), has greatly promoted the development of organic solar cells (OSCs), with PCEs...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 94 publications
(126 reference statements)
0
3
0
Order By: Relevance
“…23,24 Terminal acceptors can be classified into two types based on their performances to yield a high J SC (short-circuit current density) and (or) a high V OC (opencircuit voltage). The effective combination of a terminal group exhibiting a high J SC and another terminal group with a substantial V OC has successfully minimized energy losses, consequently enhancing power conversion efficiencies, as reported by Liu et al 20 In a comparative analysis between symmetric and asymmetric complexes, it is reported by Gopikrishna et al that introducing asymmetry to the terminal acceptor of the IPC-BEH-IC2F complex resulted in a power conversion efficiency of 12.70%, surpassing the efficiencies of the symmetrical acceptors IPC-BEH-IPC (7.26%) and IC2F-BEH-IC2F (11.05%) when blended with a PBDB-T polymer. 19 A balanced opencircuit voltage and short-circuit current is observed in the asymmetric compound IPC-BEH-IC2F, which lies in between the two symmetrical acceptors IPC-BEH-IPC and IC2F-BEH-IC2F.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…23,24 Terminal acceptors can be classified into two types based on their performances to yield a high J SC (short-circuit current density) and (or) a high V OC (opencircuit voltage). The effective combination of a terminal group exhibiting a high J SC and another terminal group with a substantial V OC has successfully minimized energy losses, consequently enhancing power conversion efficiencies, as reported by Liu et al 20 In a comparative analysis between symmetric and asymmetric complexes, it is reported by Gopikrishna et al that introducing asymmetry to the terminal acceptor of the IPC-BEH-IC2F complex resulted in a power conversion efficiency of 12.70%, surpassing the efficiencies of the symmetrical acceptors IPC-BEH-IPC (7.26%) and IC2F-BEH-IC2F (11.05%) when blended with a PBDB-T polymer. 19 A balanced opencircuit voltage and short-circuit current is observed in the asymmetric compound IPC-BEH-IC2F, which lies in between the two symmetrical acceptors IPC-BEH-IPC and IC2F-BEH-IC2F.…”
Section: Introductionmentioning
confidence: 87%
“…As cited in ref. 20, the terminal thiophene decorated small molecule acceptors displayed a high V OC and contributed to improved overall performance. Therefore, the significant enhancement observed in the symmetric A5-D1-A5 compound can be attributed to the elongation of the fused thiophene rings within the terminal acceptor moiety, which significantly enhances the V OC values as seen in our computed results summarized in Table S2 of the ESI.…”
Section: Correlation Heat Map Ratio Plotsmentioning
confidence: 98%
See 1 more Smart Citation